2022
DOI: 10.1002/iub.2665
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to prostate cancer treatments

Abstract: A review of the current treatment options for prostate cancer and the formation of resistance to these regimens has been compiled including primary, acquired, and cross-resistance. The diversification of the pathways involved and the escape routes the tumor is utilizing have been addressed. Whereas early stages of tumor can be cured, there is no treatment available after a point of no return has been reached, leaving palliative treatment as the only option. The major reasons for this outcome are the heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 228 publications
0
8
0
Order By: Relevance
“…However, while the role of GR signaling in promoting chemoresistance has been suggested for other solid tumors [ 60 , 61 , 62 ], its role in mCRPC chemoresistance just recently emerged [ 16 , 22 , 27 ]. The dual role of GR signaling in promoting resistance to both ARSI and taxane chemotherapy during the treatment of mCRPC implicates this nuclear receptor as a key player in PCa therapy cross-resistance, a common occurrence in which a pre-existing or acquired mechanism that promotes resistance to a particular drug treatment (e.g., ARSI) results in resistance to a subsequent drug or therapy (e.g., taxane chemotherapy) [ 6 , 63 ]. Therapy cross-resistance has implications for determining the safest and more effective sequence in which different drugs should be administered during PCa progression [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, while the role of GR signaling in promoting chemoresistance has been suggested for other solid tumors [ 60 , 61 , 62 ], its role in mCRPC chemoresistance just recently emerged [ 16 , 22 , 27 ]. The dual role of GR signaling in promoting resistance to both ARSI and taxane chemotherapy during the treatment of mCRPC implicates this nuclear receptor as a key player in PCa therapy cross-resistance, a common occurrence in which a pre-existing or acquired mechanism that promotes resistance to a particular drug treatment (e.g., ARSI) results in resistance to a subsequent drug or therapy (e.g., taxane chemotherapy) [ 6 , 63 ]. Therapy cross-resistance has implications for determining the safest and more effective sequence in which different drugs should be administered during PCa progression [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCa is one of the most common tumors in men. Due to its heterogeneity and progressive nature, it remains incurable ( 41 ). Valid prognostic models based on specific biomarkers can accurately predict survival outcomes for the effective management of PCa patients ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…ARV-471, which targets the estrogen receptor, is currently in a Phase II clinical trial for patients with ER+/HER2- locally advanced or metastatic breast cancer . Early results have shown that ARV-471 has a manageable safety profile and displays clinical activity, lending further support to the clinical potential of PROTACs.…”
Section: Various Types Of Protacs To Treat Hivmentioning
confidence: 99%
“…Notable among these are ARV-110 and ARV-471, both in trials for cancer treatment. ARV-110, designed to degrade the androgen receptor, is being tested in a Phase II clinical trial for metastatic castration-resistant prostate cancer . Preliminary results from the trial indicate that ARV-110 is generally well-tolerated and demonstrates potential antitumor activity, signifying a major step toward realizing the promise of PROTACs for human treatment.…”
Section: Various Types Of Protacs To Treat Hivmentioning
confidence: 99%
See 1 more Smart Citation